Radiation damage annealing in γ-irradiated amino acid crystals - Nikolov, O. T. (Biophysical Bulletin, 2018)
In the paper the processes of free radicals (FR) annealing in the γ-irradiated amino acid crystals have been studied by the electron paramagnetic resonance (EPR) method. The mechanism of the radioactive FR destruction based on the diffusion of the fragmentary radioactive vacancies or interstitial fragments is offered. The reaction of FR recombination is the secondary reason of the radioactive destruction of the crystal, a consequence of the radioactive vacancies diffusion or diffusion of the introduced fragments. The air oxygen does not play an essential role during FR destruction in amino acid crystals.